2013
DOI: 10.1155/2013/249565
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Ghrelin Administration Alters Serum Biomarkers of Angiogenesis in Diet-Induced Obese Mice

Abstract: Introduction. Ghrelin is a gastrointestinal endocrine peptide that was initially identified as the endogenous ligand of growth hormone secretagogue receptor; however, recently, the cardiovascular effect of this peptide has been indicated. In this study, we investigated the effect of ghrelin administration on serum biomarkers of angiogenesis including leptin, nitric oxide (NO), vascular endothelial growth factor (VEGF), and its soluble receptor (VEGF receptor 1 or sFlt-1) in control- and diet-induced obese mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 35 publications
0
12
0
1
Order By: Relevance
“…A streak of evidence indicates that serotonin, histamine, dopamine, and their associated receptor activities are closely associated with obesity regulation [5]. Most importantly, strong evidences are available that elicited the role of leptin, ghrelin, and neuropeptides in obesity [12][13][14]. Currently, no pharmacological treatment provides sustained weight loss with minimal adverse effects [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…A streak of evidence indicates that serotonin, histamine, dopamine, and their associated receptor activities are closely associated with obesity regulation [5]. Most importantly, strong evidences are available that elicited the role of leptin, ghrelin, and neuropeptides in obesity [12][13][14]. Currently, no pharmacological treatment provides sustained weight loss with minimal adverse effects [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study in a rat model of cardiopulmonary bypass (CPB) shows that ghrelin treatment reduces inflammatory responses, apoptosis and oxidative stress induced by CPB, and preserves the cardiac pumping function through GHS-R1a and Akt signaling (15). Increased angiogenesis is measured by changes in vascular endothelial growth factor (VEGF), VEGF receptor, and nitric oxide (NO) (45). Ghrelin treatment in rat model of MI demonstrates increased VEGF expression and angiogenesis (16).…”
Section: Introductionmentioning
confidence: 99%
“…Ghrelin treatment in rat model of MI demonstrates increased VEGF expression and angiogenesis (16). In diet-induced obese mice, systemic ghrelin treatment increases serum VEGF, and decreases NO concentrations (45). Overall, ghrelin treatment may reduce CSNA inflammation and oxidative stress in the heart, and induce angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, in the present study, 3‐week high‐dose ghrelin treatment significantly inhibited the plasma VEGF‐A levels compared with low‐dose ghrelin. However, it might remain to be seen whether ghrelin can regulate the VEGF system, because some studies reported that ghrelin promoted the VEGF system, in contrast, and inhibited the levels . Further study may be needed to establish the detailed meaning of the evaluation and regulation of circulating VEGF levels.…”
Section: Discussionmentioning
confidence: 99%